Suppressed Vascular Leakage and Myocardial Edema Improve Outcome From Myocardial Infarction - Li, Xiujuan; Redfors, Björn; Sáinz-Jaspeado, Miguel; Shi, Shujing; Martinsson, Pernilla; Padhan, Narendra; Scharin Täng, Margareta; Borén, Jan; Levin, Malin; Claesson-Welsh, Lena (Frontiers in Physiology, 2020)
Aim: The acute phase of myocardial infarction is accompanied by edema contributing to tissue damage and disease outcome. Here, we aimed to identify the mechanism whereby vascular endothelial growth factor (VEGF)-A induces myocardial edema in the acute phase of a myocardial infarction, with the aim to eventually specifically suppress VEGFA-regulated edema while preserving VEGFA-dependent collateral vessel formation. Methods and Results: VEGFA regulates vascular permeability and edema by activation of VEGF receptor-2 (VEGFR2). Activation of VEGFR2 leads to receptor autophosphorylation on tyrosine and induction of several signaling pathways, including the cytoplasmic tyrosine kinase c-Src. The activated c-Src in turn phosphorylates Vascular endothelial (VE)-cadherin, leading to dissociation of endothelial adherens junctions. A particular tyrosine at position 949 in mouse VEGFR2 has been shown to be required for activation of c-Src. Wildtype mice and mice with phenylalanine replacing tyrosine (Y) 949 in VEGFR2 (Vegfr2Y949F/Y949F) were challenged with dobutamine to induce myocardial stress, or with myocardial infarction (MI) through permanent ligation of the left anterior descending coronary artery. Vegfr2Y949F/Y949F mice coped better with stress and MI. The infarct size was similar in wildtype and mutant mice, but left ventricular wall edema and fibrinogen deposition, indicative of enhanced vascular permeability, were reduced in the Vegfr2Y949F/Y949F strain. Moreover, neutrophil infiltration and levels of myeloperoxidase were low in the infarcted mutant hearts, correlating with improved survival. In vivo tyrosine phosphorylation of vascular endothelial (VE)-cadherin at Y685, implicated in regulation of vascular permeability, was induced by circulating VEGFA in the wildtype but remained at baseline levels in the Vegfr2Y949F/Y949F hearts. Conclusion: Suppression of VEGFA/VEGFR2-regulated vascular permeability leads to diminished edema without affecting vascular density correlating with improved myocardial parameters and survival after MI.